Tropical refrigeration and air-conditioning - Cottell, Leslie W.; Olarewaju, S. ([S.l.] : Longman, 1984)
Tropical Refrigeration and Air-Conditioning covers the syllabuses of theoretical and practical Craft level examinations in refrigeration and air-conditioning. It is designed for trainee installation and service engineers and will be of permanent practical value to them in their work. Key features of the book are: * over 200 photographs and clearly labelled illustrations * glossary of important terms * sample examination papers for evaluation and revision * a 'trouble-shooting' chart for identifying and remedying defects in equipment.